LITERATUR REVIEW : PIJAT OKSITOSIN DAN AROMA TERAPI LAVENDER MENINGKATKAN PRODUKSI ASI - Tuti Tuti; Melyana Nurul Widyawati (JURNAL KEBIDANAN, 2018)
Indonesia succeeded in giving exclusive breastfeeding. Breast milk that does not come out on the first day of baby's life is one of the inhibiting factors for exclusive breastfeeding entertainment. This problem can be anticipated since pregnancy through lactation counseling. Efforts to overcome problems that cannot be done in postpartum mothers in addition to breast care are with oxytocin massage and Lavender aromatherapy. Oxytocin massage for 2-3 minutes and lavender aromatherapy is an effort that can help postpartum mothers increase milk production. Lavender contains Linalool. This substance produces effects on the central nervous system (hypothalamus) which can increase the formation of breast milk, so that it can encourage exclusive breastfeeding for newborns.Literature This review aims to find out the benefits of Oxytocin and Lavender Aromatherapy to increase milk production in post partum mothers.Journal searches were conducted electronically using several databases, namely: Science Direct, Pubmed and Google Scholar from 2008 to 2018. The key words were "Oxitocyn Massage," Aromatherapy Lavender "/ Lavender Aromatherapy" and "Breast Milk Productian". The criteria used are quantitative research, complete and complete instruments. The results of the study selected articles in national journals as many as: 8 research and international journals as many as 2 studies.            Complementary midwifery interventions in oxytocin massage along the spine (vertebrae) to the sixth-costae bone in the mother and lavender aromatherapy can be categorized as safe and effective enough in increasing breast milk production. Lavender oxytocin and aromatherapy massage can increase breast milk production